1997
DOI: 10.1038/sj.onc.1201382
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-mediated p16/CDKN2 gene transfer suppresses glioma invasion in vitro

Abstract: Malignant gliomas extensively in®ltrate the surrounding normal brain, and their di use invasion is one of the most important barriers to successful therapy. Recent studies indicate that the progression of gliomas from lowgrade to high-grade may depend on the acquisition of a new phenotype and the subsequent addition of genetic defects. One of the most frequent abnormalities in the progression of gliomas is the inactivation of tumorsuppressor gene p16, suggesting that loss of p16 is associated with acquisition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
0
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 23 publications
4
52
0
2
Order By: Relevance
“…Supporting the hypothesis of a relationship between p16 Ink4a and invasion, overexpression of p16 Ink4a in these tumor areas has been associated with other molecules that are shown to be related with invasive status (for example, the g2 chain of laminin 5 and b-catenin) (Palmqvist et al, 2000;Jung et al, 2001;Natarajan et al, 2003). Furthermore, in vitro studies have shown that p16 Ink4a is implicated in the regulation of matrix-dependent cell migration (Fahraeus and Lane, 1999), in glioma invasion (Chintala et al, 1997) and in the inhibition of breast cancer cell migration (Li and Lu, 2010).…”
Section: Other Functions Attributed To P16 Ink4amentioning
confidence: 81%
“…Supporting the hypothesis of a relationship between p16 Ink4a and invasion, overexpression of p16 Ink4a in these tumor areas has been associated with other molecules that are shown to be related with invasive status (for example, the g2 chain of laminin 5 and b-catenin) (Palmqvist et al, 2000;Jung et al, 2001;Natarajan et al, 2003). Furthermore, in vitro studies have shown that p16 Ink4a is implicated in the regulation of matrix-dependent cell migration (Fahraeus and Lane, 1999), in glioma invasion (Chintala et al, 1997) and in the inhibition of breast cancer cell migration (Li and Lu, 2010).…”
Section: Other Functions Attributed To P16 Ink4amentioning
confidence: 81%
“…This could indicate that p16 INK4a is involved in regulating infiltrative behavior independently of Rb. p16 INK4a has been suggested to inhibit tumor cell invasion and migration, [13][14][15]24 processes that involve many cytoplasmic proteins. Cdk6 has shown to be localized to the spreading edge of human fibroblasts and could potentially be a target for inhibition of cell spreading by G1-associated kinase inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Besides cell cycle control, p16 INK4a has been implicated in other processes such as senescence 10,11 and apoptosis. 12 In addition, p16 INK4a has shown to reduce cell invasion, 13,14 cell spreading 15 and angiogenesis. 16 Nonmelanoma skin cancers (NMSC) include both squamous cell carcinoma and basal cell carcinoma, and we have earlier reported that in basal cell carcinoma there is a phenotypic change from a proliferative behavior in the center of the tumor towards a less proliferative but infiltrative phenotype at the invasive front of the tumor.…”
mentioning
confidence: 99%
“…In vitro G1 cell cycle arrest induced by adenovirus-mediated p16 gene transfer showed enhanced radiation-induced cell killing by a possibly non-apoptotic mechanism, 11 and restoration of the wild-type p16 activity into p16-null SNB19 glioma cells significantly inhibited tumor-cell invasion. 12 Similarly, downregulation of integrin a(v)b (3) expression and integrin-mediated signaling in glioma cells by adenovirus-mediated transfer of antisense urokinase-type plasminogen activator receptor and sense p16 genes resulted in decreased integrin-mediated biological effects, including adhesion, migration, proliferation and survival, supporting the therapeutic potential of simultaneously targeting urokinase-type plasminogen activator receptor and p16 in gliomas. 13,14 However, G1 cell arrest induced by p16 gene transfer in glioma cells resulted in chemoresistance to some cytocidal drugs such as cisplatin or ACNU that require Figure 1 Examples of retrovirus-mediated or non-replicating adenovirus-mediated gene transfer to cancer cells.…”
Section: Non-proliferating Virusesmentioning
confidence: 89%